Mechanical behavior of loose high-strength bolted connections with thin sheet steels. (November 2021) - Xue, Xiaolei; Lin, Shentong; Guo, Zhan; Zhao, Yang; Lin, Quan; Chen, Yu
Abstract: High-strength bolted connections have attracted increasing attention over the past few decades because they can safely transfer the design load. However, the effect of the preload loss on the mechanical behavior of the bolted connections has not been investigated sufficiently, This paper presents an experimental investigation of the bearing capacity of high-strength bolted connections with loose bolts (lacking pretension force). The tests investigated ninety specimens with loose bolts and six specimens without loose bolts for comparison. The results showed that bolt fracture was the only failure mode for all of the tested connections under uniaxial tension. The global behavior of the tested connections exhibited four stages, and the features of each stage were summarized. The connections with different tightening conditions exhibited a similar trend in terms of strain development around the bolt holes. The effect of the slip coefficient, position and number of loose bolts, and the plate thickness is elucidated through parametric studies. It is found that the yield load of high-strength bolted connections may be affected by the pretension force and the slip coefficient, while the effect of the slip coefficient gradually decreases with the increasing number of loose bolts. The experimental results are compared to the calculated ultimate bearing resistance according to the GB 50017, Eurocode 3, and AISC 360-16 standards. It is found that the resistance prediction of the standards may be too conservative for the prediction of the ultimate bearing capacity of loose high-strength bolted connections when bolt fracture governs failure. Practical design recommendations in the algebraic form are presented and verified to predict the yield load and ultimate bearing capacity of loose high-strength bolted connections. Highlights: Experimental study on the mechanical behavior of loose bolted connection was conducted. The test parameters included loose bolts, slip coefficient, and plate thickness. Full-range distribution of strain near bolt hole was analyzed. Formulae that accurately predicts the yield load and the ultimate bearing capacity are developed.